ENHANCEMENT OPERATION SYSTEM MODEL MANAGING LOCAL RESOURCES-BASED ENVIRONMENT TOWARDS SUSTAINABLE DEVELOPMENT - Triono Edy (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
In manifesting the sustainable development, this work found a new paradigm in sustainable development which is based on the local resources. In This paper discussed at exploring an appropriate model in managing environment that may accommodate and optimize local resources, such as human resources and natural resources. This is important to create and maintain the sustainable development for all. detail, it elaborates and discusses some core components of the model of sustainable development that includes: (i) ontology; (ii) epistemology; and (iii) axiology of sustainable development. development could be found in Pancasila, the principle five, that is social justice for all Indonesian constitution 1945, The ontological element of sustainable article 28 h that guarantee the healthy environment for all. While the epistemological level, this work will coherency all diametrical policies and norms or regulations that related to the situation, such as environmental law, investment law, mining law, agrarian law, forestry law, marine and coastal law, and so forth. should be embodied in the appropriate mechanism and operational model, that cover the implementation, control, All those elements evaluation, development and recovery stages. In the end, this work offers an appropriate model for creating local resources based-environmental management that guaranteeing the sustainable development for all.*** This paper is aimed at creating the right model in the management and utilization of sustainable natural resources. Even to create a sustainable model of natural resource management and also focuses on optimizing local resources. This case is important given the use of local resources, both of human and natural in environmental management can ensure the sustainability of conservation and utilization of the environment [1]. The logical reason that can be put forward is that local people know in detail about the condition of the area and have both emotionally and physically related in The aim product of sustainable development and utilization of the environment based on local resources becomes the answer to the development process that has been done by the government with the only emphasis on growth [3]. It is as if the development is only intended for growth to growth. Amartya Sen believes that an event should be aimed at creating an environment (realm) that allows everyone to convert its potential to functional. Pancasila, Local Resources, Sustainable Development.